PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH MELALUI BANK SAMPAH DI KECAMATAN BANJARMASIN UTARA - Sesilia Leluni Malera; Ghinia Anastasia Muhtar (JURNAL ILMIAH RESEARCH STUDENT, 2026)
The waste problem in Banjarmasin City, particularly in North Banjarmasin District, has become increasingly complex along with the rising volume of waste generation reaching 40,193.3 tons per year. This study aims to measure the level of community participation in waste management through waste banks in North Banjarmasin District and to identify the influencing factors. The research employed a quantitative descriptive approach with a sample of 100 respondents determined using the Slovin formula with a 10% error margin and proportional random sampling technique across 10 sub-districts. Data collection was conducted through questionnaires using a five-point Likert scale, observation, and documentation. The research instrument was tested using Pearson Product Moment validity test and Cronbach's Alpha reliability test. Data analysis was performed using quantitative descriptive methods through mean calculation and class intervals. The results showed that the overall level of community participation in waste management through waste banks in North Banjarmasin District was in the low category with an average score of 2.49. Labor participation (2.77) and material participation (2.82) fell into the medium category, while intellectual participation (2.30), skill participation (2.16), and social participation (2.38) remained in the low category. The low level of community participation was caused by insufficient socialization, training, communication between waste bank managers and the community, as well as limited forums for aspirations. This study concludes that community participation in North Banjarmasin District is practical in nature and has not yet developed optimally in intellectual, skill, and social aspects. Enhanced socialization, waste management training, community empowerment, and strengthened communication between waste bank managers, government, and the community are needed to optimize participation.